MACROSTRUCTURES AND SUPERSTRUCTURES PATTERNS OF JOKOWI’S SPEECHES - Anggini Pratiwi; Refnaldi Refnaldi (English Language and Literature, 2018)
Presidential speech is one of the mushrooming issues nowadays. By applying different point of view in analyzing, the objective of this research was to figure out the patterns of Jokowi’s speeches in form of Macrostructure and Superstructure. The subjects of this research were 13 speeches in English and Indonesian. In addition, this research applied two levels in text analysis in Van Dijk’s Design, Macrostructure and Superstructure. The results of the research showed that the implementation of text analysis in Van Dijk’s Design was believed to be effective to improve the speeches. This research, in consequence, concerns with the study of critical discourse analysis in Text Analysis. This study was intended to analyze the transcription of Jokowi’s speeches. The text analysis was based on Van Dijk’s design in which the unit elements of the analysis are divided into three parts: macro-structure, superstructure and microstructure. The ones which have been analyzed in this paper are limited and focused only in; Macrostructure (Thematic) and Superstructure (Schematic). This research, thus, tries to examine on how speeches are structured and organized locally turn by turn. The result of the analysis revealed that several sentences in Jokowi’s speeches were less coherent in term of stating theme. Then, in superstructure, the scheme of the speech consisted of opening, content and closing.